ABCB1 Polymorphisms and Cold Pressor Pain Responses: Opioid-Dependent Patients on Methadone Maintenance Therapy. Issue 2 (March 2017) - Zahari, Zalina; Lee, Chee Siong; Ibrahim, Muslih Abdulkarim; Musa, Nurfadhlina; Mohd Yasin, Mohd Azhar; Lee, Yeong Yeh; Tan, Soo Choon; Mohamad, Nasir; Ismail, Rusli
Abstract : Background: Methadone is a substrate of the P-glycoprotein efflux transporter, which is encoded by ABCB1 ( MDR1 ), and thus, ABCB1 polymorphisms may influence the transport of methadone at the blood–brain barrier, affecting its adverse effects. Objectives: This study investigated the association between ABCB1 polymorphisms and cold pressor pain responses among opioid-dependent patients on methadone maintenance therapy (MMT). Methods: Malay male opioid-dependent patients receiving MMT ( n = 148) were recruited. Cold pressor pain responses (pain threshold, pain tolerance, and pain intensity) were measured at 0, 2, 4, 8, 12, and 24 hours post-methadone dose. DNA was extracted from whole blood and genotyped for ABCB1 polymorphisms including 1236C>T (rs1128503), 2677G>T/A (rs2032582), and 3435C>T (rs1045642) using the allelic discrimination real-time polymerase chain reaction. Repeated-measure analysis of variance between-group analysis was used to compare the three cold pressor pain responses and ABCB1 polymorphisms (1236C>T, 2677G>T/A, and 3435C>T) according to genotypes and allelic additive models, genotype dominant and recessive models, haplotypes, and diplotypes. Results: Patients with 2677 GG or 2677G allele had the lowest pain threshold compared with 2677G>T/A genotypes or alleles ( p = . 007 and .002, respectively). Haplotype analysis showed a significant association between ABCB1 haplotypes and pain threshold ( p = . 02). Patients with 2677G allele had the lowest pain tolerance compared to those with 2677T and 2677A alleles ( 2677G < 2677T < 2677A allele carriers; p = . 05). In terms of pain intensity scores, patients with 2677 GG or 2677G allele had the highest scores compared to other 2677G>T/A genotypes or alleles ( p = . 04 and .008, respectively). Haplotype analysis revealed a significant difference between patients with CGC haplotype and those without this haplotype ( p = . 02). Discussion: To the best of our knowledge, this study provides the first evidence that ABCB1 polymorphisms are associated with cold pressor pain responses among Malay male patients with opioid dependence on MMT. The results may provide an initial prediction on heightened pain sensitivity or hyperalgesia for individuals who are carriers of the ABCB1 polymorphisms.